2008
DOI: 10.1007/s00340-008-3021-7
|View full text |Cite
|
Sign up to set email alerts
|

Bulk crystal growth and efficient diode-pumped laser performance of Yb3+:Sc2SiO5

Abstract: A bulk crystal of Yb:Sc 2 SiO 5 (Yb:SSO) with favorable thermal properties was successfully obtained by the Czochralski method. The energy level diagrams for Yb:SSO crystal were determined by optical spectroscopic analysis and semi-empirical crystal-field calculations using the simple overlap model. The full width at half maximum of the absorption band centering at 976 nm was calculated to be 24 nm with a peak absorption cross-section of 9. Table 1.As indicated in Table 1, Sc 2 SiO 5 crystal with characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 10 publications
(11 reference statements)
0
46
0
Order By: Relevance
“…Self-pulsed Yb:GSO lasers were achieved with low pumping threshold from 1091nm to 1105 nm . Efficient diode-pumped laser performance of Yb:SSO was demonstrated with slope efficiency of 45% and output power of 3.55W (Zheng et al, 2008). The passive mode-locking and cw lasing performance of Yb:SSO was carried out in an x-fold cavity end-pumped by a 978 nm single emitter.…”
Section: Laser Peformance Of Yb Doped Silicate Crystalsmentioning
confidence: 99%
“…Self-pulsed Yb:GSO lasers were achieved with low pumping threshold from 1091nm to 1105 nm . Efficient diode-pumped laser performance of Yb:SSO was demonstrated with slope efficiency of 45% and output power of 3.55W (Zheng et al, 2008). The passive mode-locking and cw lasing performance of Yb:SSO was carried out in an x-fold cavity end-pumped by a 978 nm single emitter.…”
Section: Laser Peformance Of Yb Doped Silicate Crystalsmentioning
confidence: 99%
“…Considerable attention has also been paid to oxyorthosilicates Yb:Lu 2 SiO 5 (LSO), Yb:Y 2 SiO 5 (YSO), Yb:Gd 2 SiO 5 (GSO) and Yb:Sc 2 SiO 5 (SSO) [10][11][12][13]. It has been ascertained that single oxyorthosilicate crystals possess good optical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other Yb 3+ -doped materials, Yb:SSO exhibits good thermal conductivity (7.5 W·m −1 ·K −1 ), relatively high emission cross-sections (7.4×10 −21 cm 2 ), and broad gain bandwidths (54 nm) [12] , indicating its potential use for the development of tunable and high average power CW lasers. However, previous studies on Yb:SSO crystal have concentrated on the mode-locked regime and only few reports have referred to CW operation.…”
mentioning
confidence: 99%
“…However, previous studies on Yb:SSO crystal have concentrated on the mode-locked regime and only few reports have referred to CW operation. Zheng et al demonstrated a CW Yb:SSO laser with maximum output power of 3.55 W and slope efficiencies of 45% and 44.5%, respectively [12,13] . Tan et al demonstrated a CW Yb:SSO laser with a maximum output power of 2.73 W and a slope efficiency of 70% [14] .…”
mentioning
confidence: 99%